KONVERGENSI SIMBOLIK DAN SENSE OF COMMUNITY PADA KELOMPOK GAMER DOTA 2 - Agustinus Mega Kurniatmastria; Hapsari Dwiningtyas Sulistyani (Interaksi Online, 2021)
The advancement of internet and communication technologies encouraged the growth of virtual groups. In the meanwhile, video games were getting more common and popular to be played. Virtual groups based on video games bloomed because of these two things. Budak MMR is one of the many existing video game based virtual groups. This phenomenon of video game based virtual groups growth can be considered something new. Both virtual and gamer groups are not completely understood and misconceptions about them are not uncommon. This research tries to grasp the sense of community and converged symbolic fantasies as the result of interactions occurring inside Budak MMR, a virtual group based off a video game namely Dota 2. This research is a qualitative research with an autoethnography method which uses the researcher’s experience as a research subject. The theories used in the research are sense of community theory, symbolic convergence theory, and group cohesivity. In-depth interview on a few members of Budak MMR and narrative reflections were used as the measures of collecting data. The findings show that sense of community exists in Budak MMR, from the element of membership, influence, fulfillment of needs, to emotional connection. Fantasies from symbolic convergence in Budak MMR take form in inside jokes, role-playing, and speech codes. Jokes told there are jokes concerning happening situations and also jokes about sensitive matters. Role-playing in Budak MMR is mainly about interaction between lecturer and students. Speech code used there is about status and emotional expression. This research also found few implications on sense of community and convergence symbolic theory.